Construction at Work: Multiple Identities Scaffold Professional Identity Development in Academia - Bentley, Sarah V.; Peters, Kim; Haslam, S. Alexander; Greenaway, Katharine H. (Frontiers in Psychology, 2019)
Identity construction — the process of creating and building a new future self — is an integral part of a person’s professional career development. However, at present we have little understanding of the psychological mechanisms that underpin this process. Likewise, we have little understanding of the barriers that obstruct it, and which thus may contribute to inequality in career outcomes. Using a social identity lens, and particularly the Social Identity Model of Identity Change (SIMIC), we explore the process of academic identity construction among doctoral students. Through thematic analysis of semi-structured interviews with 22 PhD candidates, we observe that the identity construction process relies on a person’s perception of a navigable pathway between their current self and their future self. Importantly, participants who were able to access multiple identity resources were more likely to perceive a navigable pathway to a future professional self (e.g., as an academic), unless they perceived these identities to be incompatible with those held by leading members of the profession (e.g., their supervisors). This research suggests that the identities that people are able to access as they progress in their careers may play an important role in their ongoing professional identity construction and career success.